2020
DOI: 10.1016/j.eats.2019.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Ulnar Collateral Ligament Reconstruction Technique Utilizing Suture Tape Augmentation

Abstract: The prevalence of ulnar collateral ligament injuries and reconstructions among overhead throwing athletes has significantly risen in recent years. Surgical reconstruction has become the main treatment modality for athletes who have failed conservative treatment and wish to return to their sport. There has been an increased interest in graft augmentation in ligament reconstruction surgeries as surgeons search for ways to decrease the chance of graft failure. Augmented graft techniques have been described for ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The use of tapes for augmentation in reconstruction with grafts has been implemented in reconstructions of the anterior cruciate ligament, medial patellofemoral ligament, and ulnar collateral ligament of the elbow among others. 14 , 5 , 11 In biomechanical studies, 2 augmentation with ultra-high-molecular-weight tapes has demonstrated a decrease in the elongation and rupture of the graft, particularly in those of smaller size, as is the case of the graft used in this case. Although there is a potential for suture cutout at the bone tunnels, to our knowledge, this has not yet been reported when using sutures for graft augmentation, and cortical density of the sternum and the medial clavicle would make suture cutout unlikely in a young patient.…”
Section: Discussionmentioning
confidence: 92%
“…The use of tapes for augmentation in reconstruction with grafts has been implemented in reconstructions of the anterior cruciate ligament, medial patellofemoral ligament, and ulnar collateral ligament of the elbow among others. 14 , 5 , 11 In biomechanical studies, 2 augmentation with ultra-high-molecular-weight tapes has demonstrated a decrease in the elongation and rupture of the graft, particularly in those of smaller size, as is the case of the graft used in this case. Although there is a potential for suture cutout at the bone tunnels, to our knowledge, this has not yet been reported when using sutures for graft augmentation, and cortical density of the sternum and the medial clavicle would make suture cutout unlikely in a young patient.…”
Section: Discussionmentioning
confidence: 92%
“…The technique for MUCL reconstruction has been modified with various techniques including the docking technique and the modified Jobe technique [5]. A relatively new modification to current techniques includes a synthetic graft augmentation with cross-linked suture tape meant to achieve a stronger construct and to decrease the chance of graft failure [6].…”
Section: Introductionmentioning
confidence: 99%